1990
DOI: 10.1523/jneurosci.10-08-02850.1990
|View full text |Cite
|
Sign up to set email alerts
|

Carboxypeptidase E (enkephalin convertase): mRNA distribution in rat brain by in situ hybridization

Abstract: Carboxypeptidase E (CPE), also referred to as enkephalin convertase or carboxypeptidase H (EC 3.4.17.10), is present in neurotransmitter secretory granules and can remove C-terminal basic residues following endopeptidase cleavage during peptide processing. Using in situ hybridization with 35S-labeled oligonucleotide probes, we have mapped the localization of CPE mRNA in the rat brain. Specificity for CPE was confirmed by control experiments, which included production of identical patterns hybridization with 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
1

Year Published

1991
1991
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 36 publications
4
14
1
Order By: Relevance
“…Posttranslational processing of peptide hormones may be accomplished by the QC characterized here and may represent part of a regulated pathway of secretion, whereas a different form of the enzyme may be involved in the constitutive secretion of proteins such as immunoglobulins. The observed distribution of QC mRNA in the central nervous system contrasts with the corresponding data reported for the processing enzymes PAM (30) and carboxypeptidase H (31) as well as Kex2-related proteins such as PC1 and PC2 (32), which are considered as putative processing enzymes exhibiting endoproteolytic activity. On the basis of Northern blots, all proteins mentioned above are widely distributed in the brain; however, especially high expression in pituitary and hypothalamus-areas of active peptide synthesis-appears to be a common feature.…”
Section: '-Gg(c/g/ T/a)gc(t/c)gt(g/c)ga(t/c)tggac(a/c)ca(a/ G)ga(a/g)contrasting
confidence: 99%
See 1 more Smart Citation
“…Posttranslational processing of peptide hormones may be accomplished by the QC characterized here and may represent part of a regulated pathway of secretion, whereas a different form of the enzyme may be involved in the constitutive secretion of proteins such as immunoglobulins. The observed distribution of QC mRNA in the central nervous system contrasts with the corresponding data reported for the processing enzymes PAM (30) and carboxypeptidase H (31) as well as Kex2-related proteins such as PC1 and PC2 (32), which are considered as putative processing enzymes exhibiting endoproteolytic activity. On the basis of Northern blots, all proteins mentioned above are widely distributed in the brain; however, especially high expression in pituitary and hypothalamus-areas of active peptide synthesis-appears to be a common feature.…”
Section: '-Gg(c/g/ T/a)gc(t/c)gt(g/c)ga(t/c)tggac(a/c)ca(a/ G)ga(a/g)contrasting
confidence: 99%
“…The putative signal sequence and the protein sequence determined by Edman degradation are separated by the sequence (Gly-)Val-Arg-Arg (amino acids [28][29][30][31]. Since a pair of arginine residues is recognized as a typical cleavage site for posttranslational processing, it is suggested that this sequence is a propeptide sequence removed during maturation.…”
Section: '-Gg(c/g/ T/a)gc(t/c)gt(g/c)ga(t/c)tggac(a/c)ca(a/ G)ga(a/g)mentioning
confidence: 99%
“…Comparing the expression profile of the main processing enzymes between the mouse choroid plexus tissue and the mouse hypothalamus, which served as positive control, we demonstrated the presence of mRNA for all tested enzymes. The presence of mRNA and protein for Furin, CPE, and PAM1 in the rat choroid plexus cells were demonstrated (31)(32)(33)(34). The above expression profile, together with our functional neuroanatomical data (c-Fos activation) and the behavioral and physiological changes, strongly support the capacity of the choroid plexus cells to produce biologically active peptides.…”
Section: Discussionsupporting
confidence: 70%
“…In addition, all samples were amplified using the same master mixture, which contained all components of the reaction except for the template. (23). Since IP3R-II and IP3R-IV were so similar in the membrane-spanning regions, we used probes specific for the nonconserved region for IP3R-IV localization.…”
Section: Methodsmentioning
confidence: 99%